Formulasi dan Uji Antioksidan Sediaan Krim Ekstrak Etanol Buah Asam Cikala (Etlingera elatior (Jack) R. M. Sm) sebagai Pelembab Kulit - Sudewi; Nilsya Febria Zebua; Siti Arum Widiyanti; Muflihah Fujiko; Nurul Karimah; Supran Hidayat; Rahma Yulia (LPPM STIKes Indah Medan, 2022)
Cikala acid fruit is fruit of kecombrang plant (Etlingera elatior) which phenolic compounds including flavonoids and has strong antioxidants activity. Antioxidants are nutrients in the form of vitamins and minerals that function to prevent and repair damaged body tissues. Antioxidant compounds are generally used in cosmetic products. The purpose of this study to determine the antioxidant activity of the ethanolic extract of the cikala fruit was formulated into a moisturizing cream. This research is experimental, covering extract manufacture, phytochemical screening, manufacture and testing of cream preparations as well as testing of antioxidant activity in moisturizing cream. The cream formulation formula was made with a concentration ratio of 1.5%, 2%, 2.5% and blank. Chemical compounds from the ethanolic extract of cikala fruit are alkaloids, saponins, flavonoids and triterpenoids; has a homogeneous cream dosage form with a pH range of 5.7-6.1 after short storage and 12 weeks of storage; and has antioxidant activity with inhibitor concentration value of 19.92 g/mL at concentration 2.5%.